Simplify:
$(x^2 - 2y^2) (x + 4y)x^2y^2$

AcademicMathematicsNCERTClass 8

Given:

$(x^2 - 2y^2) (x + 4y)x^2y^2$

To do:

We have to simplify the given expression.

Solution:

$(x^2 - 2y^2) (x + 4y)x^2y^2=[x^2 (x + 4y) -2y^2 (x + 4y)]x^2y^2$

$= (x^3 + 4x^2y - 2xy^2 - 8y^3) x^2y^2$

$= x^2y^2(x^3) + x^2y^2(4x^2y)+x^2y^2(-2xy^2) + x^2y^2(-8y^3)$

$= x^{2+3}y^2+4x^{2+2}y^{2+1} - 2x^{2+1}y^{2+2} - 8x^2y^{2+3}$

$= x^5y^2 + 4x^4y^3-2x^3y^4 - 8x^2y^5$

raja
Updated on 10-Oct-2022 13:19:30

Advertisements